2019
DOI: 10.1186/s12889-019-6744-y
|View full text |Cite
|
Sign up to set email alerts
|

HIV leadership programming attendance is associated with PrEP and PEP awareness among young, gay, bisexual, and other men who have sex with men in Vancouver, Canada

Abstract: Background Young gay, bisexual, and other men who have sex with men (YGBM) may have reduced engagement and knowledge of HIV care and biomedical HIV prevention strategies, such as pre-exposure prophylaxis (PrEP), post-exposure prophylaxis (PEP), and Treatment as Prevention (TasP), compared with adult GBM. We sought to understand differences in HIV prevention awareness, health care access, and service utilization between youth (16–29 years) and adult (≥30 year) GBM, as well as factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The two-phase mixed-method study ( 30 ) included a cross-sectional survey with a self-administered questionnaire and a prospective descriptive study using an in-depth interview, but data needed were collected in the quantitative survey phase. Another study used a longitudinal cohort study to evaluate the impact of HIV leadership programs, and its baseline survey provided the data we needed ( 31 ). All of the remaining quantitative studies were cross-sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two-phase mixed-method study ( 30 ) included a cross-sectional survey with a self-administered questionnaire and a prospective descriptive study using an in-depth interview, but data needed were collected in the quantitative survey phase. Another study used a longitudinal cohort study to evaluate the impact of HIV leadership programs, and its baseline survey provided the data we needed ( 31 ). All of the remaining quantitative studies were cross-sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported much lower levels of awareness (<40%) among MSM in China ( 33 ); MSM tested in community centers in Portugal ( 38 ) MSM receiving rapid HIV testing in Spain ( 39 ), and among black MSM in the United States ( 13 ). Nine studies reported modest PEP awareness: 41.23% among men engaging in condomless anal sex with men in the United States ( 8 ), 42.5% among MSM in Beijing, China ( 16 ), 46.67% among gay and bisexual men in California ( 40 ), 50% among MSM in Brazil ( 41 ), 56.70% among sexually active MSM in Vancouver, Canada ( 31 ), 57.06% among MSM in Vancouver, Canada ( 42 ), 60.22% among Thai MSM ( 30 ), 60.6% among MSM in four cities of China ( 43 ), and 65.77% among HIV-positive MSM in England ( 44 ). There was significant heterogeneity between studies (Q statistic = 1990.122, I 2 = 99.045; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Engaging young and marginalised populations in health care, including HIV care and prevention, is acknowledged as difficult. 16,26,27 We also know that in New Zealand, disclosure of sexuality and sexual practices is difficult for many gay and bisexual men. [28][29][30] Given these difficulties, health-care environments must be carefully planned to ensure appropriate delivery of services.…”
Section: Discussionmentioning
confidence: 99%